Method for testing wall surface slippage of polymer melt

Through the combination of particle tracer method and Raman spectroscopy, the start time, velocity and shear strain of the wall slip of polymer melt are measured, and the research on the wall slip mechanism during the solidification of polymer melt in the prior art is solved. The problem provides new methods and theoretical foundations to help regulate the appearance and performance of injection molded products.

CN119164794APending Publication Date: 2024-12-20KINGFA SCI & TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411246007.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The prior art is difficult to effectively study the mechanism of wall slippage during the solidification process of polymer melt, especially during the solidification process of crystalline melts and amorphous melts, and it is difficult for traditional methods to accurately locate the wall layer and study shearing. Effects of crystallization behavior in the field on wall slippage.

Method used

The particle tracking method combined with the shear heat table and optical microscope is used to observe the motion trajectory of the traced particles, measure the start time, velocity and critical shear strain of the wall surface, and use Raman spectroscopy to test the crystallinity to reveal the wall surface sliding. The mechanism of movement.

Benefits of technology

This method can effectively detect the wall slip characteristics during the solidification process of crystalline polymers and amorphous polymers, provide a new method and theoretical basis for studying wall slips of solid-state melts, and help regulate the appearance and performance of injection molded products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119164794A_ABST
    Figure CN119164794A_ABST
Patent Text Reader

Abstract

The invention discloses a method for testing wall slippage of a polymer melt, and belongs to the technical field of high polymer material detection. According to the test method disclosed by the invention, the surface slippage of the sample is focused and observed by using a particle tracer method and a microscope focusing function, the temperature and the shearing field are controlled by using a shearing hot stage, and the crystallinity is tested by using a Raman spectrum; the method can effectively detect the wall surface slippage starting time, the wall surface slippage speed and the wall surface slippage critical shear strain in the solidification process of the crystalline polymer melt and the amorphous polymer melt, and is beneficial to revealing a wall surface slippage mechanism. The testing method disclosed by the invention is simple, can provide a theoretical basis for regulating and controlling the appearance of a polymer injection molding product, and provides a new method and a theoretical basis for researching the wall surface slippage of a solid-like melt.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer material detection, and in particular to a method for testing the wall slip of a polymer melt. Background Art

[0002] Injection molding is a commonly used processing method for polymers. The polymer melt in contact with the solid surface undergoes wall slip under strong shear. The melt wall slip on the surface of the injection mold can easily lead to reduced surface finish of the product or surface defects such as light and dark tiger stripes, which seriously affect the aesthetic appearance and surface performance of the product. In addition, wall slip increases the complexity of melt flow, which brings great difficulties to controlling melt flow through runner design and polymer processing technology to regulate the microstructure and performance of the product. Therefore, revealing the melt wall slip mechanism has important application value and scientific significance.

[0003] At present, the research on wall slip of polymer materials is only focused on the molten state of polymer melts. It is generally believed that there may be two mechanisms for wall slip: adhesive failure and cohesive failure. The adhesive failure mechanism believes that the molecular chains adsorbed on the wall are desorbed under shear, causing melt slip; the cohesive failure mechanism believes that the wall adsorbed chains are difficult to desorb, but the shear action causes the wall adsorbed chains to disentangle with the adjacent layer chains, causing wall slip. The polymer molecular weight and its distribution, chain structure, wall properties (wall roughness and wall surface energy, etc.) and the interaction between the wall and the molecular chain can all affect the wall slip. The methods commonly used to study wall slip include using a rheometer to analyze the shear rate corresponding to different test gaps under a fixed shear stress to indirectly obtain the wall slip velocity and its critical shear strain, rate and stress; or using a particle tracer method to directly observe the wall slip velocity and its critical conditions. The above research is usually carried out when the polymer is in a molten state. However, in actual molding, the melt changes from a flowing liquid-like state to a solid-like state with poor fluidity due to a decrease in temperature. This liquid-solid transition causes changes in the wall slip conditions. In addition, the temperature of the polymer melt in a solid-like state is low, and the microstructure formed during the molding process is easier to retain. Therefore, it is more meaningful to study the effect of polymer melt solidification on wall slip in the later stage of processing.

[0004] The actual injection molding process highlights the importance of studying the wall slip mechanism during the transformation of polymer melts to quasi-solid melts (including the transformation of crystalline polymer melts from molten state to crystalline state and the solidification of amorphous polymer melts), but the current research on the wall slip of polymer melts during solidification is almost blank. In addition, the characteristics of wall slip in crystalline melts determine the need to develop methods for simultaneous research on wall slip and crystallization behavior. Previous studies using particle tracer methods to observe wall slip have not only difficulty in accurately locating the wall layer, but also difficulty in studying crystallization behavior and its influence on wall slip behavior in shear fields.

[0005] In view of this, this application is filed. Summary of the invention

[0006] The present invention aims to provide a new method for testing the wall slip of polymer melts, which can effectively test the wall slip starting time, wall slip velocity and critical shear strain of wall slip during the solidification process of crystalline polymer melts and amorphous polymer melts.

[0007] To achieve the above object, the technical solution adopted by the present invention is:

[0008] A method for testing the wall slip of a polymer melt comprises the following steps:

[0009] Providing a detection device, the detection device at least comprising a shear heat stage and an optical microscope;

[0010] Providing a polymer sample to be tested, the surface of which contains tracer particles, and a tracer particle sample;

[0011] Setting shearing conditions, and obtaining the motion trajectories of the tracer particles and the tracer particle samples on the surface of the polymer sample to be tested respectively through the detection device;

[0012] According to the motion trajectory and shear conditions of the tracer particles and the tracer particle samples on the surface of the polymer sample to be tested, the wall slip starting time, the wall slip velocity and the critical shear strain of the wall slip are obtained.

[0013] The process of polymer molten melt transforming to quasi-solid melt (solidification) includes the transformation of crystalline polymer melt from molten state to crystalline state, and also includes the solidification process of amorphous polymer melt. The test method of the present invention utilizes particle tracing method and focuses on and observes the surface slip of the sample with the help of microscope focusing function, uses shear hot stage to control temperature and shear field, and uses Raman spectroscopy to test crystallinity, which can effectively detect the wall slip start time, wall slip velocity and critical shear strain of wall slip in the solidification process of crystalline polymer melt and amorphous polymer melt, and helps to reveal the wall slip mechanism. The test method of the present invention is simple and low in cost, provides a theoretical basis for regulating the appearance of polymer injection molded products, and provides a new method and theoretical basis for studying the wall slip of quasi-solid melt.

[0014] Preferably, the polymer sample to be detected comprises a polymer and an auxiliary agent, and the mass ratio of the polymer to the auxiliary agent is (20-100): (0-80).

[0015] Preferably, the auxiliary agent includes at least one of an antioxidant, a toughening agent, a mineral powder, a lubricant, a colorant, a weathering agent, an antistatic agent, a flame retardant, an ultraviolet light absorber, a nucleating agent and the like.

[0016] The antioxidant may include but is not limited to thioester antioxidants, hindered phenol antioxidants, hydroxylamine antioxidants, phosphite antioxidants, phosphate antioxidants and combinations thereof.

[0017] The toughening agent includes but is not limited to ethylene-octene copolymer, SEBS, maleic anhydride grafted POE, maleic anhydride grafted SEBS and combinations thereof.

[0018] The mineral powder includes but is not limited to calcium carbonate, mica, kaolin, magnesium hydroxide, boehmite and combinations thereof.

[0019] The colorant includes but is not limited to carbon black, titanium dioxide, zinc sulfide, iron red, titanium yellow and combinations thereof.

[0020] Wherein, the lubricant includes but is not limited to polyethylene wax, fatty acid ester, hyperbranched amide and a combination thereof.

[0021] The weathering agent includes but is not limited to hindered amine light stabilizers, benzotriazole ultraviolet light absorbers and combinations thereof.

[0022] Wherein, the antistatic agent includes but is not limited to zinc oxide, manganese dioxide, chromium trioxide and a combination thereof.

[0023] The flame retardant includes but is not limited to brominated polymers (e.g. brominated polystyrene), metal dialkyl phosphites (e.g. aluminum tris(diethylphosphite)), metal hydroxides (e.g. magnesium hydroxide), aromatic phosphates (e.g. resorcinol di(diphenyl phosphate) ester and bisphenol A di(diphenyl phosphate) ester) and combinations thereof.

[0024] The ultraviolet light absorber includes, but is not limited to, hydroxybenzophenones, hydroxybenzotriazoles, hydroxybenzotriazines, cyanoacrylates, nano-scale inorganic materials (eg, titanium oxide, cerium oxide, and zinc oxide), and combinations thereof.

[0025] Preferably, the polymer includes one of a crystalline polymer and an amorphous polymer.

[0026] The crystalline polymer refers to a polymer in which polymer chains are regularly arranged and stacked to form a three-dimensional ordered crystal structure.

[0027] The crystalline polymer includes at least one of polypropylene, polyethylene, polyamide and polyethylene terephthalate.

[0028] The non-crystalline polymer (also called amorphous polymer) refers to a polymer in which polymer chains are randomly arranged and stacked without forming a three-dimensional ordered crystal structure.

[0029] The amorphous polymer includes at least one of polystyrene, polymethyl methacrylate, polycarbonate and polyvinyl chloride.

[0030] Preferably, the present invention has no limitation on the shape of the polymer sample to be detected, but preferably it is in the form of a sheet.

[0031] The present invention has no limitation on the molding method of the polymer sample, and the polymer sample can be molded by any molding method known in the art, such as compression molding, injection molding, blow molding, extrusion molding, cast molding, etc.

[0032] The polymer sample to be detected containing the tracer particles is obtained by dropping the tracer particle solution on the surface of the polymer sample to be detected.

[0033] The tracer particle solution includes tracer particles and a solvent, and the mass ratio of the tracer particles to the solvent is 1:(10-10000).

[0034] The solvent includes at least one of water, acetone, ethanol, anhydrous ethanol, methanol, N,N-dimethylformamide, acetonitrile, dimethyl sulfoxide, cyclopentane, tetrahydrofuran, 2-methyltetrahydrofuran, ethylene nitrate, ethylene carbonate, 1,4-butyrolactone and dimethylacetamide.

[0035] The shearing conditions are set by the shearing hot stage control software, which can set dynamic and steady-state shearing modes, different shearing frequencies, shearing strain amplitudes and test gap values, and different experimental temperatures.

[0036] Preferably, the shear temperature is 150-250°C.

[0037] Wherein, the optical microscope records 1 to 1000 frames per second.

[0038] Preferably, the tracer particles include at least one of silica with a silver coating on the surface and hollow silica with a silver coating on the surface.

[0039] Preferably, the average particle size of the tracer particles is 1 to 50 μm.

[0040] Preferably, the time corresponding to the transition of the tracer particles on the surface of the polymer sample to be detected from being stationary to being moving is the starting time of the wall slip.

[0041] Preferably, the motion trajectory of the tracer particles on the surface of the polymer sample to be detected is represented by point coordinates;

[0042] If the shearing mode is dynamic shearing mode; let the coordinates of the tracer particles on the surface of the polymer sample to be detected at time t1 be (x1, y1); let the coordinates of the tracer particles on the surface of the polymer sample to be detected at time t2 be (x2, y2); the wall slip velocity V s =(y2-y1) / (x2-x1); the time t1 and the time t2 are any time after the tracer particles on the surface of the polymer sample to be detected change from static to moving;

[0043] The critical shear strain of wall slip ε=γ0-L / 2, where γ0 is the set strain amplitude, and L is 1 / 2 times the maximum movement distance reflected by the movement trajectory of the tracer particles on the surface of the polymer sample to be tested during the dynamic cycle. Plot the coordinate position of the tracer particles against time to obtain a sine or cosine curve. The maximum movement distance of the tracer particles is the movement from the crest to the trough. Let the coordinates of the two points at the crest and trough positions in half a dynamic shear cycle be (x p ,y p ) and (x t ,y t ), then L=0.5*((x p -x t ) 2 +(y p -y t ) 2 ) 0.5 .

[0044] Preferably, the shearing mode is steady-state shearing;

[0045] The wall slip velocity is calculated by the difference between the shear velocity provided by the shear heat stage reflected by the tracer particle sample and the movement velocity of the tracer particles on the surface of the polymer sample to be tested under shear action. The specific calculation method is as follows;

[0046] In the motion trajectory of the tracer particle sample, let the point coordinates of the tracer particle sample at time t3 be (x3, y3), and the point coordinates of the tracer particle sample at time t4 be (x4, y4), then the shear velocity provided by the shear hot stage is V0 = (y4-y3) / (x4-x3); let the point coordinates of the tracer particles on the surface of the polymer sample to be detected at time t5 be (x5, y5), and the point coordinates of the tracer particles on the surface of the polymer sample to be detected at time t6 be (x6, y6), then V1 = (y5-y6) / (x5-x6).

[0047] Sample wall slip velocity V s =V0-V1; when V1 is less than V0 at a certain moment, if the corresponding tracer particle displacement at that moment is S, then the strain γ at this moment is the critical shear strain of wall slip, and γ=S / test gap value H, S is calculated from the coordinates between the two starting points.

[0048] The test gap value H refers to the gap distance between the upper plate of the shear hot stage and the base below.

[0049] Preferably, when the polymer includes a crystalline polymer, the detection device also includes a Raman spectrometer, through which the Raman spectrometer is used to obtain the Raman spectrum of the polymer sample to be detected, and the change in crystallinity is measured by the change in the characteristic peak area or the Raman shift of the Raman spectrum; the crystallinity is plotted against time, and the crystallinity corresponding to the critical time of wall slip of the polymer sample to be detected is the critical crystallinity of wall slip.

[0050] Preferably, when the polymer comprises polypropylene, the critical crystallinity of wall slip = A 818 / (A 850 +A 818 ), where A 818 The Raman spectrum is at 818 cm -1 The peak area at A 850 The Raman spectrum is at 850cm -1 The peak area at .

[0051] Preferably, when the polymer includes an amorphous polymer, the detection device includes a shear heat stage and an optical microscope, and the shear heat stage is fixed to a bracket below the objective lens of the optical microscope.

[0052] Preferably, when the polymer includes a crystalline polymer, the detection device includes a shear heat stage, an optical microscope and a Raman spectrometer, wherein the shear heat stage is fixed to a bracket below the objective lens of the optical microscope; the Raman laser generated by the Raman spectrometer probe is connected to the optical path system of the optical microscope through the built-in beam splitter of the parallel light dual-port switch.

[0053] The beneficial effects of the present invention are as follows: the testing method of the present invention utilizes a particle tracer method and a microscope focusing function to focus and observe the surface slip of the sample, utilizes a shear hot stage to control the temperature and shear field, and utilizes Raman spectroscopy to test the crystallinity, which can effectively detect the wall slip start time, wall slip velocity, and critical shear strain of wall slip during the solidification process of a crystalline polymer melt and an amorphous polymer melt, and is helpful to reveal the wall slip mechanism. The testing method of the present invention is simple and low in cost, and provides a theoretical basis for regulating the appearance of polymer injection molded products, and provides a new method and theoretical basis for studying the wall slip of solid-state melts. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1 a is a light path diagram of the device for testing wall slip according to the present invention; Figure 1 b is a schematic diagram of the movement of tracer particles on the sample surface in the shear heat stage observed under an optical microscope.

[0055] Figure 2 a is an optical micrograph of the tracer particle sample in the blank experiment of Example 1, Figure 2 b is Figure 2 a is the coordinate position of the tracer particle marked by the box at different times on the X and Y axes. Figure 2 c is Figure 2 a The movement speed of the tracer particles marked by the box under dynamic shear.

[0056] Figure 3 a is an optical micrograph of tracer particles on the surface of the polypropylene sample of Example 1, Figure 3 b is Figure 3 a The coordinate positions of the tracer particles marked by the box on the X and Y axes at different times.

[0057] Figure 4 a is the wall slip velocity V of the tracer particles on the surface of the polypropylene sample in Example 1 at different times s , Figure 4 b is the variation of critical dynamic shear strain of wall slip of polypropylene sample in Example 1 with time; Figure 4 c is the change of crystallinity of polypropylene sample with time.

[0058] Figure 5 It is the movement speed V0 of the tracer particle sample in the blank experiment under steady-state shear in Example 2.

[0059] Figure 6 a is the velocity V1 of the tracer particles on the lower surface of polystyrene under steady shear, Figure 6 b is the wall slip velocity after the polystyrene melt solidifies under steady-state shear. DETAILED DESCRIPTION

[0060] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0061] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0062] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0063] In the present application, there is no particular limitation on the specific dispersion and stirring treatment methods.

[0064] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0065] Example 1

[0066] This example uses polypropylene as a representative of crystalline polymers and studies the wall slip during the crystallization process of polypropylene melt, specifically including the following steps:

[0067] (1) Provide Figure 1 The detection device shown in a comprises a shear heat stage, an optical microscope and a Raman spectrometer. The shear heat stage is fixed to a bracket below the objective lens of the optical microscope, and the objective lens of the optical microscope is aligned with the quartz glass window of the shear heat stage ( Figure 1 a), through which the sample can be observed; the Raman laser signal is connected to the optical microscope optical path system through a parallel light dual-port switch with a built-in beam splitter, that is, the Raman laser and the optical microscope optical path are the same ( Figure 1 a); The parallel light dual-port switch is installed below the optical microscope camera; since the Raman laser is almost co-focused with the light source of the optical microscope, the microscope focusing function can be used to simultaneously obtain the clearest observation field and the strongest Raman signal; after being reflected by the sample surface, the Raman laser returns along the incident light path ( Figure 1 a), enters the receiver in the Raman laser probe, thereby realizing the test of the crystallinity of the sample at different times.

[0068] (2) Polypropylene with the brand name Y26 produced by Sinopec was selected as the research object. Polypropylene Y26 and antioxidant were blended at a mass ratio of 1000:2 at 200°C and 60 rpm for 12 minutes. The polymer material containing the antioxidant was pressed at 250°C for 7 minutes using a flat plate vulcanizer to obtain a sheet sample.

[0069] (3) Prepare a solution of silver-plated hollow silica and anhydrous ethanol at a ratio of 1:1000, drop the solution on the surface of the sheet sample, and place it on the shear hot stage base ( Figure 1 b);

[0070] (4) After the anhydrous ethanol on the surface of the polymer sample evaporates, fasten the upper half of the shear hot stage to the base, adjust the height of the shear hot stage so that the objective lens is focused on the sample surface and the tracer particles on the sample surface can be clearly observed in the field of view;

[0071] The dynamic shearing mode was set, and the shearing frequency ω and the shearing strain amplitude γ0 were set to 0.1 Hz and 10% respectively (the relationship between the shearing strain and time can be expressed as γ = γ0sin (ωt)). The temperature of the shearing hot stage and the experimental control procedures were as follows: the shearing hot stage was heated to 200°C, and the distance between the upper plate and the base of the shearing hot stage was adjusted to 1mm. After the temperature was kept constant for 5 minutes to eliminate the thermal history of the sample, the temperature of the shearing hot stage was reduced to 132°C at 30°C / min, and the shearing action was started. The motion trajectory and crystallization information of the tracer particles on the surface of the sample under the conditions of crystallization at 132°C and shearing were recorded respectively.

[0072] (5) Drop the tracer particles directly into the observation hole of the quartz glass for observation as a blank experiment without adding a sample. Use the same shearing conditions as those used in (4) above to record the trajectory of the tracer particles at the window position of the shear hot stage base. Figure 2 As shown in the figure, the trajectory of the tracer particles in the blank experiment is represented by point coordinates using image processing software ( Figure 2 b) and calculate its movement speed ( Figure 2 c), in this embodiment, select Figure 2 The tracer particles marked by the box in a were analyzed.

[0073] (6) Use image processing software to analyze the movement of tracer particles on the sample surface. Figure 3 The tracer particles marked by the box in a are analyzed. Observe the video captured by the camera. If the tracer particles change from static to moving, the time corresponding to the change is the starting time of wall slip.

[0074] In this embodiment, the initial wall slip time is 458 s.

[0075] Let the coordinates of the tracer particles on the surface of the polymer sample to be detected at time t1 be (x1, y1); let the coordinates of the tracer particles on the surface of the polymer sample to be detected at time t2 be (x2, y2); the wall slip velocity V s =(y2-y1) / (x2-x1); the time t1 and the time t2 are any time after the tracer particles on the surface of the polymer sample to be detected change from static to moving, and the wall slip velocity V s ( Figure 4 a) is equal to the tracer particle trajectory ( Figure 3 b) The slope calculated from the coordinates of the last two adjacent time points.

[0076] The critical shear strain of wall slip ε = γ0-L / 2, where γ0 is the set strain amplitude and L is 1 / 2 times the maximum movement distance reflected by the motion trajectory of the tracer particles on the surface of the polymer sample to be tested during the dynamic period. Plot the coordinate position of the tracer particles on the surface of the polymer sample to be tested against time to obtain a sine or cosine curve ( Figure 3 b), the maximum movement distance of the tracer particles on the surface of the polymer sample to be tested is from the peak to the trough. Let the coordinates of the two points at the peak and trough positions within half a dynamic shear cycle be (x p ,y p ) and (x t ,y t ), then L=0.5*((x p -x t ) 2 +(y p -y t ) 2 ) 0.5 The critical shear strain amplitude of wall slip in each dynamic cycle is calculated from the point coordinates as Figure 4 As shown in b.

[0077] After the crystallization of polypropylene, at 846cm -1 The peak at 818 cm -1 and 850cm -1 The Raman spectrum obtained simultaneously with the shear experiment is 818cm -1 With 850cm -1 The peaks were separated and the areas of the two peaks were A 818 and A 850 . 818 / (A 850 +A 818 ) increases with the increase of crystallinity, so A 818 / (A 850 +A 818 ) describes the change in crystallinity. 818 / (A850 +A 818 )The maximum value calculated is 1; 846cm -1 Split to 818cm -1 and 850cm -1 The calculated value at the critical time corresponding to the two peaks is 0; that is, for A 818 / (A 850 +A 818 ) was normalized to obtain the relative crystallinity in the range of 0 to 100%, and the relative crystallinity was plotted against the time recorded by the Raman spectrometer ( Figure 4 c), the relative crystallinity corresponding to the wall slip starting time (458s calculated above) is the critical crystallinity of wall slip. In this embodiment, the critical crystallinity of wall slip is 47.6%.

[0078] Example 2

[0079] This example uses polystyrene as a representative of non-crystalline polymers and studies the wall slip during the solidification process of polystyrene melt, specifically including the following steps:

[0080] (1) Providing a detection device, the detection device comprising a shear heat stage and an optical microscope, wherein the shear heat stage is fixed to a bracket below the objective lens of the optical microscope;

[0081] (2) Polystyrene with a brand number of 430102 purchased from Sigma-Adrich Company was selected as the research object, and it was blended with an antioxidant at a mass ratio of 1000:2 at 200°C and a speed of 50 rpm for 12 minutes, and the polymer material containing the antioxidant was pressed at 200°C for 7 minutes using a flat plate vulcanizer to obtain a sheet sample;

[0082] (3) Prepare a solution of hollow silica with silver coating on the surface and anhydrous ethanol at a ratio of 1:1000, and drop the solution on the lower surface of the sheet sample placed on the base of the shear hot stage. Since polystyrene is highly transparent, the movement of tracer particles on the lower surface of the sample in the shear hot stage can be observed;

[0083] (4) After the anhydrous ethanol on the surface of the polymer sample evaporates, fasten the upper part of the shear hot stage to the base, adjust the height of the shear hot stage so that the objective lens is focused on the sample surface and the tracer particles on the lower surface of the sample can be clearly observed in the field of view;

[0084] Set the steady-state shear mode, set the shear hot stage rotation angular velocity to 0.005rad / s, and the temperature of the shear hot stage and the experimental control procedures are as follows: Heat the shear hot stage to 200℃, adjust the shear hot stage test gap value to 1mm, and keep the temperature constant for 3min to form good adhesion between the sample and the upper and lower quartz glasses; reduce the shear hot stage temperature to 115℃ at 30℃ / min, and start to apply shear and record the movement trajectory of the tracer particles on the sample surface.

[0085] (5) Drop the tracer particles directly into the observation hole of the quartz glass for observation as a blank experiment without adding a sample. Use the same shear conditions as those used in (4) above to record the trajectory of the tracer particles at the window position of the shear hot stage base. Use image processing software to calculate the movement speed of the tracer particles in the blank experiment ( Figure 5 ), the average value of the tracer particle movement velocity V0 in this embodiment is 0.038 mm / s.

[0086] (6) Use image processing software to analyze the movement of tracer particles on the lower surface of the polystyrene sample. Observe the video captured by the camera. If the movement speed of the tracer particles is less than the speed of the tracer particles in the blank experiment at a certain moment, then this moment corresponds to the starting time of wall slip. In this embodiment, the starting time of wall slip is about 74s ( Figure 6 a), the corresponding displacement S of the tracer particle on the lower surface of the sample is 2.78 mm, and the critical strain of wall slip γ = S / H = 278%, where the test gap H is 1 mm. The average value of the tracer particle movement velocity in the blank experiment is 0.038 mm / s minus the observed movement velocity V1 on the lower surface of the polystyrene sample ( Figure 6 a), the wall slip velocity V of the solidified polystyrene can be obtained s ( Figure 6 b).

[0087] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for testing the wall slip of a polymer melt, characterized in that: The following steps are involved: Providing a detection device, the detection device at least comprising a shear heat stage and an optical microscope; Providing a polymer sample to be tested, the surface of which contains tracer particles, and a tracer particle sample; Setting shearing conditions, and obtaining the motion trajectories of the tracer particles and the tracer particle samples on the surface of the polymer sample to be tested respectively through the detection device; According to the motion trajectory and shear conditions of the tracer particles and the tracer particle samples on the surface of the polymer sample to be tested, the wall slip starting time, the wall slip velocity and the critical shear strain of the wall slip are obtained.

2. The polymer melt wall slip test method according to claim 1, characterized in that: The polymer sample to be detected comprises a polymer and an auxiliary agent, and the mass ratio of the polymer to the auxiliary agent is (20-100): (0-80).

3. The testing method for polymer melt wall slip according to claim 2, characterized in that: The polymer includes a crystalline polymer and an amorphous polymer.

4. The method for testing the wall slip of a polymer melt according to claim 1, characterized in that: The tracer particles include at least one of silica with silver coating on the surface and hollow silica with silver coating on the surface.

5. The method for testing the wall slip of a polymer melt according to claim 1, characterized in that: The time corresponding to the transition of the tracer particles on the surface of the polymer sample to be detected from being stationary to being moving is the wall slip start time.

6. The method for testing the wall slip of a polymer melt according to claim 1, characterized in that: The motion trajectory of the tracer particles on the surface of the polymer sample to be detected is represented by point coordinates; If the applied shear is a dynamic shear mode, let the coordinates of the tracer particles on the surface of the polymer sample to be detected at time t1 be (x1, y1); let the coordinates of the tracer particles on the surface of the polymer sample to be detected at time t2 be (x2, y2); wall slip velocity Vs = (y2-y1) / (x2-x1); the time t1 and time t2 are any moments after the tracer particles on the surface of the polymer sample to be detected change from static to moving; wall slip critical shear strain ε = γ0-L / 2, wherein γ0 is the set strain amplitude, and L is 1 / 2 times the maximum movement distance reflected by the movement trajectory of the tracer particles on the surface of the polymer sample to be detected within the dynamic period; plot the coordinate position of the tracer particles on the surface of the polymer sample to be detected against time to obtain a sine or cosine curve, and the maximum movement distance of the tracer particles is the movement from the crest to the trough, and let the coordinates of the two points at the crest and trough positions within half a dynamic shear period be (x p ,y p ) and (x t ,y t ), then L=0.5*((x p -x t ) 2 +(y p -y t ) 2 ) 0.5 .

7. The method for testing the wall slip of a polymer melt according to claim 1, characterized in that: When the shearing mode is steady-state shearing, the wall slip velocity is calculated by the difference between the shear velocity provided by the shear heat stage reflected by the tracer particle sample and the movement velocity of the tracer particles on the surface of the polymer sample to be tested under shearing. The specific calculation method is as follows; In the motion trajectory of the tracer particle sample, let the point coordinates of the tracer particle sample on the surface of the polymer sample to be detected at time t3 be (x3, y3), and the point coordinates of the tracer particle sample at time t4 be (x4, y4), then the shear velocity provided by the shear hot stage is V0 = (y4-y3) / (x4-x3); let the point coordinates of the tracer particle on the surface of the polymer sample to be detected at time t5 be (x5, y5), and the point coordinates of the tracer particle on the surface of the polymer sample to be detected at time t6 be (x6, y6), then V1 = (y5-y6) / (x5-x6), and the wall slip velocity V s =V0-V1; when V1 is less than V0 at a certain moment, if the corresponding tracer particle displacement at that moment is S, then the strain γ at this moment is the critical shear strain of wall slip, and γ=S / test gap value H, S can be calculated from the coordinates between the two starting points.

8. The method for testing the wall slip of a polymer melt according to claim 3, characterized in that: When the polymer includes a crystalline polymer, the detection device also includes a Raman spectrometer, which obtains the Raman spectrum of the polymer sample to be detected through the Raman spectrometer, and measures the change in crystallinity by the change in the characteristic peak area or Raman shift of the Raman spectrum; the crystallinity is plotted against time, and the crystallinity corresponding to the critical time of wall slip of the polymer sample to be detected is the critical crystallinity of wall slip.

9. The method for testing the wall slip of a polymer melt according to claim 3, characterized in that: When the polymer includes an amorphous polymer, the detection device includes a shear heat stage and an optical microscope, and the shear heat stage is fixed to a bracket below the objective lens of the optical microscope.

10. The method for testing the wall slip of a polymer melt according to claim 3, characterized in that: When the polymer includes a crystalline polymer, the detection device includes a shear heat stage, an optical microscope and a Raman spectrometer, wherein the shear heat stage is fixed to a bracket below the objective lens of the optical microscope; the Raman laser generated by the Raman spectrometer probe is connected to the optical path of the optical microscope through a beam splitter built into the parallel light dual-port switcher.